A new species of Cosmocercoides (Nematoda; Cosmocercidae) and other helminths in Leptodactylus latrans (Anura; Leptodactylidae) from Argentina - DRAGHI,REGINA (2020)
Abstract Cosmocercoides latrans n. sp. (Cosmocercidae) from the small intestine of Leptodactylus latrans (Anura: Leptodactylidae) from Northeastern Province of Buenos Aires, Argentina is described. The new species can be distinguished from their congeners by a combination of the characters, among which stands out the number of rosette papillae, the lack of gubernaculum and the presence of lateral alae in both sexes. There are over 20 species in the genus Cosmocercoides, and Cosmocercoides latrans n. sp. represents the third species from the Neotropical realm and the second for Argentina. Additionally, seven previously known taxa are reported; Pseudoacanthocephalus cf. lutzi, Catadiscus uruguayensis, Rauschiella palmipedis, Aplectana hylambatis, Cosmocerca parva, Schrankiana sp. and Rhabdias elegans; providing literature records and information on distribution and host-parasite relationships.